How to Reduce Agricultural Subsidies From EU Funds - Friedrich Heinemann (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2017)
"EU agricultural policy seems anachronistic. There is no justification for its dominant position in the EU budget," says Professor Friedrich Heinemann, head of ZEW's Research Department "Corporate Taxation and Public Finance" and author of the new ZEW study in cooperation with Bertelsmann Stiftung. ZEW is a network partner of EconPol Europe, the European Network for Economic and Fiscal Policy Research. Furthermore, agricultural subsidies have a very poor precision in supporting poor farmers. Very rich farmers also benefit from income support, despite the fact that their income levels exceed the eligibility thresholds in the individual national welfare states. For this reason, the new ZEW study recommends reducing the costs of agricultural subsidies through significant national contributions to agricultural support. "If the Member States wish to privilege their farmers over other economic sectors, they should do so without passing the burden onto European taxpayers," explains Friedrich Heinemann. On 28 June 2017, EU Commissioner for Budget and Human Resources Günther Oettinger proposed the introduction of a "national co-financing scheme" in agricultural policy. "Oettinger's proposal is a first step in the right direction.," explains Heinemann: "If the Member States are required to participate in the financing of this questionable subsidy policy, this could increase pressure for reform in agricultural policy."
Keywords: 330